Extension of the Best Constant Approximation Operator in Orlicz Spaces. (25th April 2020) - Favier, Sergio; Lorenzo, Rosa
Abstract: In this article we deal with the best φ -approximation operator by constants extended from an Orlicz space L φ ( Ω ) to the space L ψ + ( Ω ), where ψ + denotes the right derivative of the function φ . We obtain pointwise convergence for a suitable class of functions. Also we consider a maximal operator which allows as to get modular convergence for a specific class of Orlicz spaces.